Characteristics and outcome of patients set up on high-flow oxygen therapy at home. (October 2019) - Dolidon, Samuel; Dupuis, Johann; Molano Valencia, Luis-Carlos; Salaün, Mathieu; Thiberville, Luc; Muir, Jean-François; Cuvelier, Antoine; Patout, Maxime
Background: High-flow oxygen therapy (HFOT) is increasingly used for acute respiratory failure. Few data support its use at home for the treatment of chronic respiratory failure. Our aim was to report the pattern of the use of long-term HFOT in our center and the outcome of patients setup on long-term HFOT. Methods: A retrospective monocentric study including all patients setup on long-term HFOT between January 2011 and April 2018 in Rouen University Hospital was carried out. Patients were divided into two groups, patients with hypoxemic respiratory failure treated with nasal HFOT (nHFOT) and tracheotomized patients treated with tracheal HFOT (tHFOT). Results: A total of 71 patients were established on long-term HFOT. Out of these 43 (61%) were included in the nHFOT group and 28 (39%) were included in the tHFOT group. In the nHFOT group, underlying respiratory diseases were interstitial lung disease ( n = 15, 35%), pulmonary hypertension ( n = 12, 28%), lung cancer ( n = 9, 21%), and chronic airway disease ( n = 7, 16%). In the tHFOT group, the number of admissions for exacerbation decreased by −0.78 per year (–2 to 0) ( p = 0.045). In total, 51 (72%) patients were discharged to their homes and 20 (28%) went to a post-acute re-enablement facility. Median survival following HFOT was 7.5 months. Survival was significantly lower in the nHFOT group with a median survival of 3.6 months whereas median survival was not reached in the tHFOT group ( p < 0.001). Monthly costs associated with home delivery of HFOT were €476 (296–533) with significant differences in costs between the nHFOT group of €520 (408–628) and costs in the tHFOT group of €296 (261–475) ( p < 0.001). Conclusions: The use of long-term HFOT allows very severe patients to be discharged at a reasonable cost from acute care facilities. The reviews of this paper are available via the supplementary material section.